Comparative Analysis of Agricultural Business Models, Innovative Tools and Techniques Across Different Countries: A Review - Yadav, Vikash; Bihari, Bankey; Devi Deen Yadav (International Journal of Social Sciences Review, 2025)
Agriculture is a crucial global sector, though its operational frameworks differ significantly across countries, providing sustenance, employment and raw materials for various industries. This study examines agricultural business models, focusing on technology integration, governmental interventions, market dynamics and cultural influences. Through case studies from the United States, China, India, Brazil and the Netherlands, it highlights the strengths, weaknesses, and unique features of diverse agricultural systems. Key factors such as land availability, labor dynamics, environmental imperatives and trade policies shape these practices and frameworks. Innovation, including precision farming, automation and biotechnology, plays a pivotal role in enhancing productivity and sustainability.Developing countries like India are characterized by smallholder farming, traditional methods and diverse crops. Agriculture serves as a primary livelihood source, but challenges such as fragmented landholdings, poor infrastructure and limited market access hinder modernization. While government initiatives aim to support farmers and promote sustainability, persistent issues like land tenure, water management and rural-urban migration remain barriers to growth. The study underscores the diversity of agricultural business models shaped by historical, institutional and market factors. Technological innovation, sustainable practices and market integration emerge as critical drivers of development. Advancements like precision agriculture—utilizing IoT devices, drones and satellite imagery—optimize resource use, enhance yields and reduce environmental impact. Effective policies, rural infrastructure investments and multi-stakeholder collaborations are essential for resilient agricultural systems that address socio-economic and environmental challenges, ultimately contributing to global food security, economic prosperity and environmental sustainability